A cDNA library from the antenna of Monochamus alternatus Hope and binding properties of odorant‐binding proteins. (20th May 2014) - Gao, X.; Wang, M.‐Q.
Abstract Chemoreception is a key feature in selection of host plants by insects. We performed a preliminary functional characterization of olfactory proteins isolated from an antennal cDNA library of Monochamus alternatus. We identified four olfactory genes, including two encoding putative classic odorant‐binding proteins (OBPs) and two encoding minus‐C OBPs. We expressed two of the four OBPs, MaltOBP3 and MaltOBP5, in a bacterial system and assessed their ligand specificity by measuring the competitive binding of fluorescent probe, N‐phenyl‐1‐naph‐thylamine, in the presence of 17 volatile beetle‐ or host‐plant‐related ligands. The results indicated that although MaltOBP3 and MaltOBP5 bound a distinctly different group of competitors, both had relatively high binding affinities (Ki < 20 μm) for certain compounds. The differences in their binding affinities towards host‐plant ligands suggest the roles of MaltOBP3 and MaltOBP5 in host‐plant selection.